(untitled) (International journal of artificial intelligence, 2025)
Different factors have different effects on the formation of children's scientific outlook. Among these factors, the development of creative and mathematical thinking is the most important. After all, the process of formation of imagination and concepts in a child begins in the preschool institution, and this period is the most important stage in terms of the content of the formation of worldview.